Platelet rich plasma and mechanical loading in regenerative tendon repair - Zargar Baboldashti, N (2011)
Tendon injuries and tendinopathy are a growing problem in the aging but physically active population as well as athletes. Tendons have highly ordered matrix and undergo complex changes during the remodelling phase of tendon healing. Moreover, anaerobic metabolism and poor vascular network contribute to slow adaptation of tissue to the remodelled matrix which consequently results in slow and compromised healing. Such a destitute and slow healing process necessitates development of new and effective therapies and to combine therapies to obtain possibly synergistic effects. Addressing this clinical requirement, the work presented in this thesis investigates the role of two emerging treatment options, platelet rich plasma (PRP) and mechanical loading, on tendon healing. The effects of PRP, a rich autologous source of growth factors, on tendon cells was studied by modelling important stages of tendon healing in vitro. Key parameters such as cellular migration, chemotaxis, viability and senescence were investigated by means of different culturing and staining techniques together with microscopic analyses. PRP significantly increased migration and chemotaxis in human primary tenocyte culture. Moreover, PRP protected human tenocytes against challenging environments created by known tendon damaging drugs, dexamethasone and ciprofloxacin, as well as the injury relevant condition of hypoxia. Concurrently, an in vitro rat tail tendon injury model and static loading device was developed to assess the effect of static mechanical loading and PRP on the biochemical and biomechanical properties of tendon at the tissue level. This in vitro system was also used to investigate the synergistic effects of PRP and mechanical loading on tendon healing. Both PRP and mechanical loading helped to improve the biomechanical and biochemical properties of damaged tendon in vitro. In conclusion, the positive effects of PRP on key cellular parameters such as cell survival, migration and chemotaxis and also mechanical and biochemical properties of tendon tissue make it an important option for faster and less invasive tendon treatment. Additionally, an in vitro tendon injury model together with the mechanical loading device provide a new tool to investigate the mechanical boundary conditions suitable for treating different types of tendon disorders. The findings from the current study points towards the significant contribution of PRP and mechanical loading to the healing process in tendons and could serve as a promising starting point for developing integrated therapeutic modalities to improve the quality and speed of recovery from tendon injury.